How sensitive is a carbon-neutral power sector to climate change? The interplay between hydro, solar and wind for Portugal. (15th January 2022) - Fortes, Patrícia; Simoes, Sofia G.; Amorim, Filipa; Siggini, Gildas; Sessa, Valentina; Saint-Drenan, Yves-Marie; Carvalho, Sílvia; Mujtaba, Babar; Diogo, Paulo; Assoumou, Edi
Abstract: Climate change will impact renewable resources and electricity demand, usually not jointly considered when designing future decarbonized power systems. This paper assesses how sensitive the Portuguese carbon-neutral power sector is to climate change by 2050 and what are the implications for the formally approved Portuguese Carbon Neutrality Roadmap. The future capacity factors for wind, solar and hydropower and electricity demand response to temperature are estimated for 22 climate projections along the Representative Concentration Pathway 4.5 and 8.5. The eTIMES_PT optimization model is used to assess its combined impact on the cost-optimal configuration of the power sector by 2050. Results show that climate change lowers hydropower generation by 20% (in median terms). Improving spatial and temporal resolution and including future climate patterns, results also in lower cost-effectiveness of solar photovoltaic vis-à-vis the Carbon Neutrality Roadmap. While future climate does not impact onshore wind production, offshore wind power generation is positively affected, being a climate-resilient carbon-neutral option for Portugal. Annual electricity unitary costs at final users (excluding taxes and levies) only increase up to 4% with climate change, but seasonal costs have higher variability. This analysis highlights that climate change affects the cost-optimal annual carbon-neutral power sector and needs to be included in energy planning. Highlights: Future climate affects the optimal configuration of a carbon-neutral power system. Wind, solar and hydropower capacity factors under 22 climate projections. Wind offshore is found to be a climate resilient carbon-neutral option for Portugal. Solar PV is lower than in official carbon neutrality roadmap due to time resolution. Seasonal electricity unitary costs are highly affected by climate change.